A new dung beetle genus with two new species from Chile (Coleoptera: Scarabaeidae: Scarabaeinae) - Vaz-De-Mello, Fernando Z.; Halffter, Gonzalo (Zootaxa, 2006)
A new scarabaeine genus (Tesserodoniella n. gen.) with two new species (T. elguetai n. sp. and T. meridionalis n. sp.) from Chile are described, and provisionally included in the tribe Canthonini. Species in the new genus are most similar to species from two Australian genera and appear not to be closely related to other New World canthonines.